Perbedaan Tingkat Self-Efficacy Akademik Siswa Ditinjau dari Aspek Jenis Kelamin serta Implikasinya dalam Bimbingan dan Konseling - Wahid, Ahmad; Firman, Firman; Netrawati, Netrawati (Program Studi Bimbingan dan Konseling Islam, 2024)
With good academic self-efficacy will give students the ability to try harder, overcome challenges and obstacles in the learning process. The focus of this study is to describe academic self-efficacy and examine the differences in academic self-efficacy from the aspect of gender. The approach used is quantitative with a comparative descriptive method. The research population was Phase E students of SMA Negeri 10 Padang, with a total of 360 students. Sample selection was carried out by proportional random sampling. After the sampling process, the sample in this study amounted to 190 students, with 95 male and female samples each. The process of collecting data by administering an academic self-efficacy scale with a Likert model, which was then tested using the Independent Sample T-test formula. The results explained that the overall condition of students' academic self-efficacy, both male and female, is currently in the high category, and the available data suggest that there is a meaningful difference in academic self-efficacy between them.